2021
DOI: 10.1186/s41039-021-00157-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring EFL learners’ inferential reading comprehension skills through a flipped classroom

Abstract: This study presents the results of a mixed-methods approach in finding the effects of the WebQuest-based flipped classroom on the EFL learners’ inferential reading comprehension skills. A group of EFL learners attending an IELTS course participated in the study. T-test and one-way repeated measures ANOVA were used to analyze the quantitative data. The results showed that the WebQuest-based flipped classroom effectively developed the learners’ inferential reading comprehension skills, and its long-term effect w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 46 publications
6
39
0
1
Order By: Relevance
“…e results based on the questionnaire reveal that the participants had favourable perceptions and attitudes towards the flipped instructed studying technique. e findings of the current research paper are in line with the findings reported by Samiei and Ebadi [39], Sosa Díaz et al…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…e results based on the questionnaire reveal that the participants had favourable perceptions and attitudes towards the flipped instructed studying technique. e findings of the current research paper are in line with the findings reported by Samiei and Ebadi [39], Sosa Díaz et al…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, students showed motivation to master the grammar of English through learning as well as teaching in the flipped classroom since mastering the grammar of English in the flipped instructed classes allows them to communicate with different learners more effectively. According to Samiei and Ebadi [39], students have the positive attitudes developing reading comprehension skills in the flipped classroom.…”
Section: Discussionmentioning
confidence: 99%
“…The student's readiness for using technology significantly supports self-regulation skills to stimulate satisfaction and academic achievements. A similar study found a positive attitude towards technology by enhancing reading comprehension skills [9]. This study highlights that utilization of technology can ultimately stimulate higher-order thinking skills.…”
Section: Introductionsupporting
confidence: 67%
“…Samiei, F., and Ebadi, S. (2021) [45] Investigating the effects of the WebQuest-based flipped classroom on the EFL learners' inferential reading comprehension skills.…”
Section: Mixed (Quasi-experimental) 49mentioning
confidence: 99%